Key antecedents of brand equity in heritage brand extensions: The moderating role of tourist heritage experience - M. Belén Prados-Pe\~na; Salvador del Barrio-García (European Research on Management and Business Economics (ERMBE), 2021)
This study examines how the degree of fit between the brand extension and the parent brand, in the case of heritage sites, affects the extension's brand equity-formation, considering the mediating role of brand attitude and brand credibility and the moderating role of the tourist's level of experience of the parent heritage brand. An experimental design is applied, in which two different levels of fit between the parent heritage brand and the brand extension are controlled between subjects. Suggestions are provided for effective ways of enhancing heritage brand equity and therefore contributing to destination promotion and competitiveness.
Keywords: M30; M31; M37; 650; Brand equity; Brand extension; Brand attitude; Brand credibility; Experience; Destination brand equity